Effects of Histone Deacetylase Inhibitor on Extracellular Matrix Production in Human Nasal Polyp Organ Cultures. Issue 1 (January 2013) - Cho, Jung-Sun; Moon, You-Mi; Park, Il-Ho; Um, Ji-Young; Kang, Ju-Hyung; Kim, Tae Hoon; Lee, Sang Hag; Kang, Hee Joon; Lee, Heung-Man
Background: Nasal polyposis is associated with a chronic inflammatory condition of the sinonasal mucosa and involves myofibroblast differentiation and extracellular matrix (ECM) accumulation. Epigenetic modulation by histone deacetylase (HDAC) inhibitors including trichostatin A (TSA) has been reported to have inhibitory effects on myofibroblast differentiation in lung and renal fibroblasts. The purpose of this study was to investigate the inhibitory effect of TSA on myofibroblast differentiation and ECM production in nasal polyp organ cultures. Methods: Nasal polyp tissues from 18 patients were acquired during endoscopic sinus surgery. After organ culture, nasal polyps were stimulated with TGF-beta1 and then treated with TSA. Alpha-smooth muscle actin (α-SMA), fibronectin, and collagen type I expression levels were examined by reverse transcription–polymerase chain reaction (PCR), real-time PCR, Western blot, and immunofluorescent staining. HDAC2, HDAC4, and acetylated H4 expression levels were assayed by Western blot. Cytotoxicity was analyzed by the terminal deoxynucleotidyl transferase biotin–dUTP nick end labeling assay. Results: The expression levels of α-SMA, fibronectin, and collagen type 1 were increased in nasal polyp after transforming growth factor (TGF) beta1 treatment. TSA-inhibited TGF-beta1 induced these gene and protein expression levels. Furthermore, TSA suppressed protein expression levels of HDAC2 and HDAC4. However, TSA induced hyperacetylation of histones H4. Treatment with TGF-beta1 with or without TSA did not have cytotoxic effect. Conclusion: These findings provide novel insights into the epigenetic regulation in myofibroblast differentiation and ECM production of nasal polyp. TSA could be a candidate of a therapeutic agent for reversing the TGF-beta1–induced ECM synthesis that leads to nasal polyp development.